IMPOLITENESS IN TV SERIES EUPHORIA: A GENDER-BASED SOCIOPRAGMATIC ANALYSIS - Meira Elok Duhita; Mangatur Nababan; Djatmika Djatmika (Universitas Duta Bangsa Surakarta, 2025)
Impoliteness in language reflects complex social dynamics, especially in audiovisual media where characters perform identity, power, and gender roles through dialogue. However, few studies have explored how gender-based impoliteness unfolds in fictional narratives, creating a gap between theory and media representations. This study investigates impoliteness strategies and gendered linguistic features in Season 1 of the TV series Euphoria. Using a qualitative descriptive method, the study analyzes 50 impolite utterances through Culpeper’s (2011) framework of impoliteness and gender theories from Lakoff (1973) and Coates (2013). Findings show that both male and female characters most frequently use the Bald on Record strategy, but female characters employ impoliteness more often. Taboo words emerge as the dominant linguistic feature across genders, with higher intensity among females. These results challenge conventional views of women as more polite or indirect speakers. In Euphoria, female characters use language typically associated with masculine speech, aggressive, explicit, and confrontational, indicating a shift in gendered communication patterns. This research highlights the urgency of viewing fictional media as a sociopragmatic lens to understand how language, gender, and power interact. It offers new insight into how media narratives can subvert traditional gender norms and reflect evolving linguistic behaviors.